Acute respiratory distress syndrome induction by pulmonary ischemia-reperfusion injury in large animal models - Fard-Rutherford, Nassim; Saffari, Arash; Emami, Golnaz; Hofer, Stefan; Kauczor, Hans-Ulrich; Mehrabi, Arianeb (Journal of surgical research, 2014)
Acute respiratory distress syndrome (ARDS) is a common critical pulmonary complication after esophagectomy and other thoracic surgeries (e.g., lung transplantation, pulmonary thromboendarterectomy). Direct pulmonary ischemia-reperfusion injury (PIRI) is known to play the main role in induction of ARDS in these cases. Large animal models are an appropriate choice for ARDS as well as PIRI study because of their physiological and anatomic similarities to the human body. With regard to large animal models, we reviewed different methods of inducing in situ direct PIRI and the commonly applied methods for diagnosing and monitoring ARDS or PIRI in an experimental research setting.